The Source/Drain Engineering of Nanoscale Germanium-based MOS Devices - Li, Zhiqiang (Springer Theses, Recognizing Outstanding Ph.D. Research, 2016)
This book mainly focuses on reducing the high parasitic resistance in the source/drain of germanium nMOSFET. With adopting of the Implantation After Germanide (IAG) technique, P and Sb co-implantation technique and Multiple Implantation and Multiple Annealing (MIMA) technique, the electron Schottky barrier height of NiGe/Ge contact is modulated to 0.1eV, the thermal stability of NiGe is improved to 600℃ and the contact resistivity of metal/n-Ge contact is drastically reduced to 3.8×10−7Ω•cm2, respectively. Besides, a reduced source/drain parasitic resistance is demonstrated in the fabricated Ge nMOSFET. Readers will find useful information about the source/drain engineering technique for high-performance CMOS devices at future technology node.